The Freudian ego and its relation to the self in American psychoanalytic theory. - Kelen, Jennifer Susan. (University of Ottawa (Canada), 1990)
This thesis finds that "the self" as a concept has been included in psychoanalytic theory but has not been emphasized. The ego is defined in this thesis as a psychoanalytic term. "The self" is defined as a philosophical concept that integrates the subject (an experiential, first person quality), and object (a sense of being an individual as a whole) in mental life. Theoretical writings on the ego are observed to separate the subject and object. In psychoanalysis, the debate on the status of the self in relationship to the ego is found to originate in the 1940s. Five areas of research indicate that while Freud did not stress "the self", he did not omit it. (1) The historical antecedents to psychoanalysis in German scientific materialism illustrate the pressure on psychoanalysis to be identified with scientific and not metaphysical thought. The mind-body relationship in German materialism formulates "the self" as a function of the body, not of the spirit. This is seen to be consistent with Freud's psychic structure in which the ego is a function of the psyche and the psyche a function of the body. (2) The pressure to affiliate with the scientific movement is also apparent in the terminological choices in early and recent English translations (cf. Jones, 1908; Strachey, 1966a). The absence of a personal reference in the translation of das Ich as "the ego" (instead of "the I") is found to detract from Freud's intention. However, when the English translation is reviewed in the context of its evolution, it was found that many decisions were the result of historical-political and cultural considerations. Latin and Greek terminology were required to ensure the survival of psychoanalytic thought. (3) A review of the conceptual development of the ego supports the assumption that Freud included a central aspect within the psyche. Physiological/structural and psychological descriptors are seen to be combined. The ambiguity in Freud's presentation of the ego is suggested to be the result of integrating these descriptors and due to Freud's focus on pathological, not normal, ego functioning. Freud's continued interest in splitting of the ego (not integration) is seen to be consistent with nineteenth century psychiatry. (4) It is also observed that the emphasis in Freudian theory is on the analysis of the psyche. Psychological synthesis was seen to follow automatically the removal of psychological obstacles. This underlying premise indicates that Freud did not ignore a central aspect within the psyche. (5) The foundation of "the self" in American psychoanalytic theory is traced to the reformulation of the ego. Modifications to the ego began with the introduction of "self-representations" (Hartmann, 1950) and led to the presentation of "the self" as a structure comparable to the id, ego and superego (Kohut, 1978; Kernberg, 1982). The basis of these changes originated in discussions of narcissism. Alterations in psychoanalytic theory are suggested to be an attempt to integrate the objective and subjective functions of "the self" within the ego. (Abstract shortened by UMI.)
Keywords: Psychology, Clinical.